Exercise benefits yourself and your offspring: a mini-review - Wang, Kun; Zhao, Jiajia; Wang, Yanqiu; Liu, Mairu (Frontiers in Cell and Developmental Biology, 2025)
Regular physical activity is widely recognized for its systemic health benefits, extending beyond physical fitness to influence metabolism, immunity, and neurophysiology. Pregnancy is a physiologically unique period characterized by dynamic immunometabolic changes that are crucial for maternal and fetal health. Maternal exercise during this window offers a non-pharmacological strategy to enhance maternal wellbeing and optimize offspring development. This review summarizes recent advances in understanding the effects of maternal exercise on both pregnant women and their offspring. In mothers, exercise improves metabolic profiles, modulates inflammatory responses, supports neuroplasticity, and promotes skeletal health. In offspring, maternal exercise confers long-term benefits including improved glucose metabolism, enhanced neurogenesis, cognitive development, and immune resilience. Mechanistically, these effects are mediated through molecular pathways such as placental superoxide dismutase 3 (SOD3) upregulation, adenosine 5′-monophosphate-activated protein kinase/ten-eleven translocation (AMPK/TET) signaling in the fetal liver, and exercise-induced circulating factors like Apelin and SERPINA3C, which contribute to epigenetic remodeling and tissue-specific programming. Despite growing evidence, gaps remain in understanding the optimal intensity, timing, and molecular mediators of maternal exercise, particularly regarding long-term immune and neurodevelopmental outcomes in offspring. Future studies leveraging multi-omics approaches are needed to elucidate cross-organ signaling mechanisms and identify therapeutic targets to mimic exercise-induced benefits. Overall, maternal exercise emerges as a safe, accessible intervention with significant potential to improve maternal-fetal health and reduce offspring disease risk across the lifespan.